Peran Guru dalam Meningkatkan Literasi Membaca Pada Siswa Sekolah Dasar - Tamala, Devi (Journal of Innovation in Teaching and Instructional Media, 2024)
Reading literacy is a basic skill that is important in supporting the academic and social development of elementary school students. This study aims to analyze the role of teachers in improving students' reading literacy, including learning methods, media use, and mentoring strategies. The study was conducted using a qualitative descriptive method involving teachers and students in several elementary schools as subjects. Data were collected through interviews, classroom observations, and document analysis. The results of the study indicate that teachers have a crucial role as facilitators, motivators, and innovators in literacy learning. The use of activity-based approaches, such as shared reading, storytelling, and literacy games, has been shown to be effective in increasing students' interest and reading ability. In addition, the use of technology, such as interactive learning applications, and the provision of an environment rich in reading materials, also supports literacy development. However, the study also found challenges, such as limited learning time, lack of access to quality reading materials, and differences in student ability levels. Therefore, ongoing training is needed for teachers to improve their competence in implementing effective literacy strategies. This study concludes that the active and adaptive role of teachers is very influential in building a strong literacy culture in elementary schools.